2019
DOI: 10.1186/s12885-019-5808-9
|View full text |Cite
|
Sign up to set email alerts
|

Blocking podoplanin suppresses growth and pulmonary metastasis of human malignant melanoma

Abstract: Background Podoplanin (PDPN), a transmembrane O -glycoprotein, is up-regulated in many tumors and is involved in tumor metastasis and malignant progression. In previous studies, we generated a functional blocking monoclonal antibody (mAb, SZ168) against the extracellular domain of human PDPN. This study is aimed to investigate whether blocking PDPN by SZ168 inhibits tumor growth and metastasis. Methods Malignant melanoma xenograft model by ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Recently, PDPN has attracted attention as a novel target antigen for the development of antibody therapy because PDPN is expressed on various refractory tumors. As a blocking antibody, the anti-PDPN neutralizing antibodies MS-1 and SZ168, which inhibit the binding of PDPN expressed on tumor cells and C-type lectin-like receptor 2 expressed on platelets, decreased tumor growth and metastasis in PDPN-overexpressed Chinese hamster ovary (CHO)-K1 cells and human melanoma cell lines xenografted onto mouse models [ 28 , 29 ]. Furthermore, the anti-human PDPN antibody, NZ-12, showed an obvious anti-tumor effect against human malignant pleural mesothelioma in an orthotopic xenograft model by inducing ADCC activity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PDPN has attracted attention as a novel target antigen for the development of antibody therapy because PDPN is expressed on various refractory tumors. As a blocking antibody, the anti-PDPN neutralizing antibodies MS-1 and SZ168, which inhibit the binding of PDPN expressed on tumor cells and C-type lectin-like receptor 2 expressed on platelets, decreased tumor growth and metastasis in PDPN-overexpressed Chinese hamster ovary (CHO)-K1 cells and human melanoma cell lines xenografted onto mouse models [ 28 , 29 ]. Furthermore, the anti-human PDPN antibody, NZ-12, showed an obvious anti-tumor effect against human malignant pleural mesothelioma in an orthotopic xenograft model by inducing ADCC activity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 To date, many studies have shown that the expression of PDPN is related to the malignancy, invasiveness, and metastasis of tumor. 7,13,14 Recently, we developed two monoclonal antibodies (mAb) against human PDPN, SZ-163, and SZ-168, and established an enzyme-linked immunosorbent assay (ELISA) to quantitate plasma soluble PDPN utilizing these two mAbs. 15 In this study, we examined plasma sPDPN levels in controls (CTL, 100 cases), patients with fibroadenomas of breast (FOB, 50 cases), and breast cancer patients (pathological type: invasive ductal carcinoma, IDC, 159 cases) were measured with the newly established ELISA method to evaluate the correlation between sPDPN and tumor occurrence and metastasis status of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Podoplanin (PDPN), a mucin-type transmembrane glycoprotein known as the marker of lymphatic endothelial cells, 3 is highly expressed in many types of cancer tissue and cells, 4 such as lung cancer, 5 , 6 malignant melanoma, 7 osteosarcoma 8 and brain gliomas. 9 PDPN is the only known endogenous ligand of the C-type lectin-like receptor 2 (CLEC-2) expressed on platelets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human SCC and malignant pleural mesothelioma cell lines, PDPN induces EMT and promotes tumor cell invasion and distant metastasis by binding with platelets [21]. Furthermore, anti-PDPN antibodies, which neutralize PDPN-platelet interaction, suppress the tumor growth and pulmonary metastasis of human melanoma and mesothelioma in a mouse model [22,23]. Therefore, it is considered that PDPN enhances tumor malignancy and thus could be used as a therapeutic target for some types of tumors.…”
Section: Introductionmentioning
confidence: 99%